2017
DOI: 10.1080/21691401.2017.1388248
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using transgenicNicotiana tabacumcallus culture expressing silicatein gene from marine spongeLatrunculia oparinae

Abstract: In the present investigation, transgenic tobacco callus cultures and plants overexpressing the silicatein gene LoSilA1 from marine sponge Latrunculia oparinae were obtained and their bioreduction behaviour for the synthesis of silver nanoparticles (AgNPs) was studied. Synthesized nanoparticles were characterized using UV-visible spectroscopy, Fourier transformed infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), atomic flame el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…At lower Ag-NPs concentrations (100 µg mL −1 ), the values of ZOIs decreased to 16.8 ± 0.3, 13.7 ± 0.2, 17.8 ± 0.3, 17.3 ± 0.3, 15.3 ± 0.1, and 19.2 ± 0.2 mm for B. subtilis, S. aureus, P. aeruginosa, K. pneumoniae, E. coli, and C. albicans, respectively (Figure 6). Shkryl et al [16] reported that the antimicrobial activity of Ag-NPs synthesized by callus extract of Nicotiana tabacum was enhanced by increasing the concentrations of NPs. Moreover, the inhibition zones that formed due to the treatment of multi-drug resistant pathogens S. aureus and P. aeruginosa with different concentrations (25, 50, 100, and 150 µL) of Ag-NPs synthesized via Catharanthus roseus callus extract were (4.0, 7.0, 16.0, and 23.0 mm) and (5.0, 9.0, 19.0, and 29.0 mm), respectively [65].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower Ag-NPs concentrations (100 µg mL −1 ), the values of ZOIs decreased to 16.8 ± 0.3, 13.7 ± 0.2, 17.8 ± 0.3, 17.3 ± 0.3, 15.3 ± 0.1, and 19.2 ± 0.2 mm for B. subtilis, S. aureus, P. aeruginosa, K. pneumoniae, E. coli, and C. albicans, respectively (Figure 6). Shkryl et al [16] reported that the antimicrobial activity of Ag-NPs synthesized by callus extract of Nicotiana tabacum was enhanced by increasing the concentrations of NPs. Moreover, the inhibition zones that formed due to the treatment of multi-drug resistant pathogens S. aureus and P. aeruginosa with different concentrations (25, 50, 100, and 150 µL) of Ag-NPs synthesized via Catharanthus roseus callus extract were (4.0, 7.0, 16.0, and 23.0 mm) and (5.0, 9.0, 19.0, and 29.0 mm), respectively [65].…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…Silver nanoparticles (Ag-NPs) have received more attention in recent decades because of their safe applications in different biomedical and biotechnological sectors [16]. Recently, Ag-NPs have been employed as antimicrobial agents, for wound healing, for anti-viral, and anti-inflammatory purposes, for the control of phytopathogenic microbes, and as anti-cancer cells and, optical receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The sample for AFM was prepared by making a suspension of AgNPs with water and the addition of a droplet onto a substrate. The air-dried suspension was scanned using an AFM instrument (FLEX-AFM, Nanosurf easyscan II controller) [39]. In order to identify the biological functional groups the dried Streptomyces sp.…”
Section: Characterizations Of Agnpsmentioning
confidence: 99%
“…This was further photographed using TEM (FEI, TECNAI G2, F30) at a magnification of × 60,000 to × 80,000 [41]. Elemental analysis was done using Energy dispersive spectroscopy (EDS) coupled with SEM to identify the metal ion concentration in AgNPs [39]. Finally, X-ray diffraction (XRD) measurements of AgNPs were performed using XRD spectroscopy (Rigaku Smartlab SE).…”
Section: Characterizations Of Agnpsmentioning
confidence: 99%
“…The first report describing how Carica papaya callus can be used for the synthesis of silver nanoparticles (AgNPs) in the range of 60-80 nm was published by Mude and coauthors [57]. Subsequently, metal nanoparticles were obtained using extracts of Taxus yunnanensis [58], Hyptis suaveolens [59], Citrullus colocynthis [60], Panax ginseng [61], Sesuvium portulacastrum [62], Linum usitatissimum [63], Nicotiana tabacum [64], and Solanum incanum [65] cell cultures. AgNPs and gold nanoparticles (AuNPs) have been produced using Michelia champaca calli [66].…”
Section: Introductionmentioning
confidence: 99%